On the diversity of ideas in academic spaces - Galea, Sandro (Frontiers in public health, 2023)
Universities and other academic spaces are social institutions that exist primarily for ideas—to generate, curate, and transmit ideas to students and to the world. Academic spaces cannot carry out that function without supporting a diversity of perspectives. At the same time, universities must reckon—as must all social institutions—with changing norms around how to engage with ideas that challenge, provoke, even anger members of the communities dedicated to their discussion. It is on these institutions to listen to and learn from these ideas, consistent with their core function, while engaging pragmatically with the challenges and controversies that can arise whenever ideas are regularly and freely aired. While there should indeed be limits to the range of tolerable expression within universities, the imposition of these limits should happen rarely, with caution and humility. It is important that academic institutions recognize that while contemporary preoccupations that influence our engagement with speech may change, the secret to universities’ durability over the centuries is that our core purpose—the generation and exploration of ideas—does, and should, not. This inherent value for societies is worth preserving, even, and particularly, in the face of societal pressure and change.